2011
DOI: 10.5173/ceju.2011.03.art16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of loss of heterozygosity in patients with urinary bladder carcinoma: neoplastic tissue vs. urine sediment cells

Abstract: IntroductionLoss of heterozygosity (LOH) is frequently observed in urinary bladder neoplasms. In the reported study, an attempt was undertaken to determine the loss of heterozygosity of TP53(17p13), RB1(13q14), CDKN2A/ ARF(9p21) genes in DNA from neoplastic tissue, collected from patients with diagnosed urinary bladder carcinoma, and to compare the results with those of LOH evaluation in DNA isolated from urine sediment cells.Material and methodsAfter isolation, DNA was amplified (PCR) by means of primers to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another well tested marker are 9 chromosome deletions and loss of heterozygosity. These are mainly the changes in NMIBC and it is possible to determine their appearance both in tumour DNA and in DNA isolated from urine sediment [ 30 , 31 , 32 ]. They are observed even in 60% of cases (also confirmed by our earlier research) and can be used for detection and monitoring of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another well tested marker are 9 chromosome deletions and loss of heterozygosity. These are mainly the changes in NMIBC and it is possible to determine their appearance both in tumour DNA and in DNA isolated from urine sediment [ 30 , 31 , 32 ]. They are observed even in 60% of cases (also confirmed by our earlier research) and can be used for detection and monitoring of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, ARID1A mutations were most frequently observed in the FGFR3WT tumors, associated with poor prognosis [26], while methylation of RASSF1A in this kind of BC correlated with higher stage and grade [27]. Furthermore, data from our previous loss of heterozygosity (LOH) study indicates that LOH of the TP53, RB1 and CDKN2A/ARF genes is more often observed in >Ta and G3 tumors [28].…”
Section: Clinopathological Parametersmentioning
confidence: 99%
“…The mutations in CHEK2 (Chekpoint Kinase, IVS2 + 1G>A, 1100delC, and I157T) gene were detected using multiplex PCR . Loss of heterozygosity (LOH) for the TP53 , /ARF, and RB1 genes was studied using PCR technique with malignant and wild‐type (blood, genomic) DNA .…”
Section: Methodsmentioning
confidence: 99%